Partial molar pregnancy associated with a normal appearing foetus: a case report and review of the literature - Singh, Sujata; Swain, Sasmita; Das, Lucy; Das, Pravat Chandra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Partial molar pregnancy is a rare entity in which there is usually a triploid abnormal foetus associated with a large placenta with cystic changes. The incidence of a normal diploid foetus and a partial molar placenta is extremely rare. Here we report a case of partial molar pregnancy in which a normal appearing foetus with diploid karyotype coexist. In this case a 24yr old primigravida at 20 week 3days gestation presented with 3-4 episodes of vaginal bleeding and generalised swelling of body since one month. On evaluation she was found to have moderate anaemia, proteinuria, raised serum β hcg and USG showed a single live foetus with thickened cystic placenta covering the internal os. After counselling patient was put up for hysterotomy. The product of conception and placenta were sent for histopathology and karyotyping which confirmed partial hydatidiform mole with trisomy 21 foetus. Patient had uneventful post op period and was followed up with serial β hcg measurement which fell to undetectable levels within two months.